The Effectiveness of Breast Care in Increasing Breast Milk Production in Postpartum Mothers - Mustikawati Mustikawati; Wd Erty Hikma; Fuzianti Lestari (GLOBAL HEALTH SCIENCE GROUP, 2026)
The postpartum period is a crucial phase for the success of exclusive breastfeeding, marked by various physiological and psychological changes in the mother. One common issue during this period is the difficulty in expressing breast milk, which can affect the baby's growth and overall health. Contributing factors include stress, fatigue, poor nutritional intake, and a lack of knowledge about proper breastfeeding techniques. Breast care is a non-pharmacological intervention that has been scientifically proven to stimulate the hormones prolactin and oxytocin, thereby enhancing milk production and expression. This study aims to evaluate the effectiveness of the breast care technique in improving breast milk production and expression in postpartum mothers. It also seeks to describe the characteristics of the respondents and compare their condition before and after the intervention. This research used a descriptive qualitative approach with a case study design involving five postpartum mothers. Respondents were selected based on specific criteria using purposive sampling. Data were collected through direct observation during a four-day breast care intervention. Before the intervention, all respondents experienced difficulties in milk expression, with scores categorized as “very low” to “low.” After four days of intervention, a significant improvement was observed. All respondents achieved the maximum score (10/10) based on maternal indicators and a good score (5/6) based on infant indicators. Breast care proved effective in enhancing milk flow through hormonal stimulation and its relaxing effect.